In-Depth Characterization of greenflesh Tomato Mutants Obtained by CRISPR/Cas9 Editing: A Case Study With Implications for Breeding and Regulation - Gianoglio, Silvia; Comino, Cinzia; Moglia, Andrea; Acquadro, Alberto; García-Carpintero, Víctor; Diretto, Gianfranco; Sevi, Filippo; Rambla, José Luis; Dono, Gabriella; Valentino, Danila; Moreno-Giménez, Elena; Fullana-Pericàs, Mateu; et al. (Frontiers in Plant Science, 2022)
Gene editing has already proved itself as an invaluable tool for the generation of mutants for crop breeding, yet its ultimate impact on agriculture will depend on how crops generated by gene editing technologies are regulated, and on our ability to characterize the impact of mutations on plant phenotype. A starting operational strategy for evaluating gene editing-based approaches to plant breeding might consist of assessing the effect of the induced mutations in a crop- and locus-specific manner: this involves the analysis of editing efficiency in different cultivars of a crop, the assessment of potential off-target mutations, and a phenotypic evaluation of edited lines carrying different mutated alleles. Here, we targeted the greenflesh (gf) locus in two tomato cultivars (‘MoneyMaker’ and ‘San Marzano’) and evaluated the efficiency, specificity and mutation patterns associated with CRISPR/Cas9 activity for this gene. The gf locus encodes a Mg-dechelatase responsible for initiating chlorophyll degradation; in gf mutants, ripe fruits accumulate both carotenoids and chlorophylls. Phenotypic evaluations were conducted on two transgene-free T2 ‘MoneyMaker’ gf lines with different mutant alleles (a small insertion of 1 nucleotide and a larger deletion of 123 bp). Both lines, in addition to reduced chlorophyll degradation, showed a notable increase in carotenoid and tocopherol levels during fruit ripening. Infection of gf leaves and fruits with Botrytis cinerea resulted in a significant reduction of infected area and pathogen proliferation compared to the wild type. Our data indicates that the CRISPR/Cas9-mediated mutation of the Gf locus in tomato is efficient, specific and reproducible and that the resulting phenotype is robust and consistent with previously characterized greenflesh mutants obtained with different breeding techniques, while also shedding light on novel traits such as vitamin E overaccumulation and pathogen resistance. This makes gf an appealing target for breeding tomato cultivars with improved features for cultivation, as well as consumer appreciation and health.